2021
DOI: 10.5194/essd-13-1167-2021
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic analysis of a decade of daily measurements of SO<sub>2</sub> emission in the troposphere from volcanoes of the global ground-based Network for Observation of Volcanic and Atmospheric Change

Abstract: Abstract. Volcanic plumes are common and far-reaching manifestations of volcanic activity during and between eruptions. Observations of the rate of emission and composition of volcanic plumes are essential to recognize and, in some cases, predict the state of volcanic activity. Measurements of the size and location of the plumes are important to assess the impact of the emission from sporadic or localized events to persistent or widespread processes of climatic and environmental importance. These observations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 61 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…The NOVAC network was established with a project funded by the European Union in the period 2005-2010, thereafter, it continued to be maintained and expanded, thanks to resources supplied from the volcano observatories initially involved in the active project. The NOVAC community currently counts about 160 stations on 47 volcanoes in different regions of the world, now including Iceland, Philippines, Indonesia, Papua New Guinea and Montserrat [60]. The present work shows the updated results of the ground-based scanning DOAS network installed at Vulcano Island Italy in 2008 (Figures 1 and 4).…”
Section: Methodsmentioning
confidence: 83%
“…The NOVAC network was established with a project funded by the European Union in the period 2005-2010, thereafter, it continued to be maintained and expanded, thanks to resources supplied from the volcano observatories initially involved in the active project. The NOVAC community currently counts about 160 stations on 47 volcanoes in different regions of the world, now including Iceland, Philippines, Indonesia, Papua New Guinea and Montserrat [60]. The present work shows the updated results of the ground-based scanning DOAS network installed at Vulcano Island Italy in 2008 (Figures 1 and 4).…”
Section: Methodsmentioning
confidence: 83%
“…It has also been shown that open-vent volcanoes are the most prodigious volcanic outgassers of volatiles into the atmosphere, worldwide (Andres and Kasgnoc 1998;Carn et al 2016). Additionally, extensive records of the outgassing fluxes of open-vent volcanoes from many decades of in situ measurements (Arellano et al 2021;Carn et al 2016;Carn et al 2017;Fioletov et al 2016) show that outgassing between eruptions dominates the volcanic gas budget (Allard 1997;Carn et al 2016;Carn et al 2017). Indeed, satellite-based global observations of SO 2 flux confirms that persistent, or passive, degassing accounts for ~ 90% of the global outgassing sulphur flux from volcanoes (Carn et al 2016;Carn et al 2017) and that most of the top 20 volcanic outgassers, as quantified from UV sensors total ozone mapping spectrometer (TOMS) and ozone mapping instrument (OMI), may be classified as 'open-vent' (Table S1; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…with backpack sized instruments); and (4) instruments can be employed in autonomous, remote, and low-maintenance measurement networks (see e.g. Galle et al, 2010;Arellano et al, 2021). In practice, these points are substantial factors making scientific environmental observations feasible.…”
Section: Instrument Mobilitymentioning
confidence: 99%